Increased sulfur-containing amino acid content and altered conformational characteristics of soybean proteins by rebalancing 11S and 7S compositions - Wang, Biao; Teng, Da; Yu, Cunhao; Yao, Luming; Ma, Xiaohong; Wu, Tianlong (Frontiers in Plant Science, 2022)
Soybean proteins are limited by their low contents of methionine and cysteine. Herein, 7S globulin accumulation was reduced using RNA interference to silence CG-β-1 expression, and the content of the A2B1a subunit was largely increased under the soybean seed-specific oleosin8 promoter. The results showed that the sulfur-containing amino acid content in soybean seeds drastically improved, reaching 79.194 nmol/mg, and the 11S/7S ratio had a 1.89-fold increase compared to the wild-type acceptor. The secondary structures of 11S globulin were also altered, and the β-sheet content increased with decreasing β-turn content, which was confirmed by Fourier transform infrared spectroscopy, Raman spectroscopy and circular dichroism analysis. Our findings suggested that raising the accumulation of 11S glycinin at the expense of reducing the content of 7S globulin is an attractive and precise engineering strategy to increase the amount of sulfur-containing amino acids, and soybean proteins with A2B1a subunits of 11S isolates improved, and β-subunits of 7S fractions reduced simultaneously might be an effective new material for food production.